Aplicación del proceso de atención de enfermería en cuidados intensivos (2010)
ABSTRACT: To describe the factors related with the application of the nursing care process (NCP) and diagnostic taxonomies, interventions and expected results in intensive care units -ICU- of Medellin. Methodology. Cross-sectional study performed in a simple of 65 nursing professionals from 12 ICU between April and June of 2007. Sociodemographic and labor variables, care methodologies, NCP application and clinical aptitude were explored; the type of institution and the existence of structured nursing reports according to the methodology were explored as well. Results. Professionals are young women with a little experience who take care doing assessment; they plan based on the medical diagnosis and follow ICU established protocols. They say they don’t apply the NCP - however they take part, assess and plan, and in a lower degree they diagnose and evaluate-, they have low clinical aptitude too. Conclusion. Nursing professionals attach importance to the NCP as a tool that gives professional identity however they don’t incorporate it as a care methodology.